Community-based education on glucose management in gemolong to prevent diabetes mellitus - Yulia Ratna Dewi; Emma Ismawatie; Resi Tondho Jimat; Yulita Maulani; Laela Siti Mustikatun (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2026)
This community service program aimed to enhance public awareness regarding the importance of blood glucose level management as an early preventive strategy against diabetes mellitus. A participatory, community-based approach was adopted, commencing with a SWOT analysis to identify local needs and priorities. The program was implemented in Gemolong Village, Sragen Regency, and involved 30 participants aged 45–70 years. The interventions comprised structured health education sessions, free blood glucose screening, and guided health discussions and consultations. The screening results indicated that 16 participants (53%) exhibited elevated blood glucose levels, while 14 participants (47%) were within normal limits. The program significantly improved participants’ understanding of diabetes risk factors and underscored the importance of early detection. In conclusion, community-based service initiatives are effective promotive and preventive measures for addressing non-communicable diseases and may serve as a sustainable cross-sectoral collaborative model to improve overall community health outcomes.